Atomic Absorption Determination of Metals in Superficial Roadside Soils Using Ultrasonic Sample Preparation - Elik, A. (Asian Journal of Chemistry, 2010)
A fast ultrasonic acid method for leaching of Pb, Mn and Ni from roadside superficial soil samples prior to determination by atomic absorption spectrometry in order to asses the pollution from motor vehicle exhaust has been examined and is shown to be beneficial in the recovery of these metals from surface soils. The best analytical conditions influencing leaching such as exposure time, acid type, acid concentration, sample amount and particle size were determined. A short exposure time (0.5 h), a mixture of concentrated HNO3-HCl (4:1, v/v), a 0.5 g sample amount (in 25 mL solvent), a particle size < 63 μm were found to be best. Comparable results for the proposed ultrasonic leaching method and the hot-plate acid digestion method for metals in certified reference material and roadside soil samples are obtained, thus indicating the possibility of using mild conditions for sample preparation instead of intensive treatments inherent with the digestion methods. Besides, this method reduces the time required for all treatments with hot-plate digestion method approximately from 14 h to 1.5 h. The precision obtained from 12 replicate ultrasonic leaching method yielded an average RSD of 1.16, 1.73 and 1.34 % for Pb, Mn and Ni, respectively, depending on the analyte. The precision of the method, together with its efficiency, rapidity, matrix free and environmental acceptability, makes it a good alternative for the determination of trace metals in soil material.